Lack of reproductive toxicity in adult male rats exposed to interferon-alpha - Rosa, Josiane de Lima [UNESP]; Cavariani, Marilia Martins [UNESP]; Borges, Cibele dos Santos [UNESP]; Leite, Gabriel Adan Araújo [UNESP]; Anselmo-Franci, Janete Aparecida; Kempinas, Wilma de Grava [UNESP] (Taylor & Francis Group content, 2015)
Interferon-alpha (IFN- α ), a type I IFN, is a protein with antiviral, antiproliferative, and immunoregulatory activities, widely used in the treatment of several types of cancers as well as hepatitis B and C. Decrease of libido and erectile dysfunction are commonly reported by male patients during treatment of chronic hepatitis C with IFN- α . However, IFN therapy-associated underlying factors attributed to sexual dysfunction are still not well defined. Currently, there are few studies investigating the effects of IFN on male reproductive system functions. Given that, the aim of the present investigation was to examine effects of subchronic exposure to IFN- α (5 × 10(4) U/kg and 10 × 10(4) U/kg, 30 d) on serum hormones, sperm parameters, fertility, and testicular and epididymal hystopathology and morphometry in adult male Wistar rats. None of the evaluated parameters was markedly altered by IFN- α . Thus, our results suggest that exposure to IFN- α , in this experimental design, did not adversely affect sperm quality and fertile capacity of male rats.